Pendampingan dan Penyuluhan Metode Perhitungan Harga Pokok Produksi Pada UMKM Desa Wanakerta, Kabupaten Tangerang - Faroqi, Fachmi Al; Atmaja, Sena; Hadi, Helmas Septiyo; Maesaroh, Siti (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Small and Medium Enterprises, which relatively have more limitations compared to large companies, especially in the financial field, need to understand the calculation of production costs in order to set selling prices accurately. The problem with Small and Medium Enterprises in Wanakerta Village is the absence of a standard format for calculating the cost of production. The calculations used so far are based only on the total raw materials for production, while other cost components have not been included in the calculation of the cost of production. Extension services are conducted through the provision of materials by the speaker and exercises in calculating the Cost of Production, accompanied by discussions. In this extension service, direct interaction between the speaker and the participants is important. Participants are invited to discuss, ask questions, and share experiences, so they can better understand the concepts being taught. The results of the extension are (1) the knowledge of Small and Medium Enterprise owners who are the subjects of the extension and production price assistance has increased from the previous condition; (2) the skills of Small and Medium Enterprise owners in calculating the cost of production using Microsoft Excel as an aid have increased from the previous condition.